Implementation of Blended Learning in Southern African Marginalised Higher Education Eclectic Contexts - Patricia Muhuro; Simon Murote Kang’ethe (Journal of Education and Learning Technology)
Unequivocally, even though blended learning is lauded for being useful in enhancing online and face-to-face learning in institutions of higher learning, little attention has been paid to interrogating its implementation in marginalised higher education contexts. Marginalised contexts include slums, rural areas, remote locations, and zones characterised by resource limitations. If contextual realities are not well considered in such settings, the implementation of blended learning may result in more marginalisation and digital exclusion. This paper therefore explored the implementation of blended learning in Southern African marginalized eclectic contexts. The study adopted the digital inclusion framework by Helsper using constructs of access, proficiency, and opportunity. The study employed a literature review method using 20 relevant studies extracted from major databases. Data were analysed using thematic analysis. The study found that blended learning can be implemented successfully when: policies are blended-learning friendly, resources are robustly usable and accessible, capacity building to facilitate functional blended learning proficiencies and curriculum design are instituted, and delivery facilitates digital inclusion. The study will be of benefit to academics, administrators, and policymakers who are looking for ways to increase blended learning delivery in their spaces.